2018
DOI: 10.1155/2018/9829208
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Sodium Treatment Ameliorates Extrapancreatic Organ Injuries in a Murine Model of Acute Pancreatitis Induced by Caerulein

Abstract: Aim We determined the effects of diclofenac sodium, octreotide, and their combination on extrapancreatic organ injuries in caerulein-induced acute pancreatitis in mice. Methods A total of 58 BALB-C male mice (25 g) were divided into seven groups and used to create a caerulein-induced acute pancreatitis model. Diclofenac sodium, octreotide, and their combination were given for treatment of caerulin-induced acute pancreatitis in mice. At the end of the experiment, the lung, liver, kidney, and stomach were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…30 Animal studies with diclofenac showed promising results with decreased pancreatic injury and decreased kidney, lung, and liver injury by reducing apoptosis and necrosis. 31,32 It was reported that 2 had acute kidney injury with diclofenac by Mahapatra et al, 15 but both these events could not be attributed to diclofenac. Four events of acute lung injury with diclofenac are seen which are less but significant when compared with 9 with tramadol.…”
Section: Discussionmentioning
confidence: 99%
“…30 Animal studies with diclofenac showed promising results with decreased pancreatic injury and decreased kidney, lung, and liver injury by reducing apoptosis and necrosis. 31,32 It was reported that 2 had acute kidney injury with diclofenac by Mahapatra et al, 15 but both these events could not be attributed to diclofenac. Four events of acute lung injury with diclofenac are seen which are less but significant when compared with 9 with tramadol.…”
Section: Discussionmentioning
confidence: 99%
“…Both the groups were comparable in terms of safety parameters. Diclofenac is a non steroidal anti inflammatory agent (Ozer Cakir & Findik, 2018). The pancreato-protective effect of diclofenac alone and in combination with sublingual nitrates and somatostatin in post-ERCP acute pancreatitis is reported in many clinical studies (Katsinelos et al, 2012;Serrano et al, 2019;Tomoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac administration was also associated with reduced extra‐pancreatic damage e.g. decreased kidney injury (Ozer Cakir & Findik, ), decreased peri‐nephric fat tissue inflammation (Ozer Cakir & Findik, ), lung injury (Bhatia et al, ; Ozer Cakir & Findik, ) and liver injury (Ozer Cakir & Findik, ). The protective effect of diclofenac is by enhancing LxA4, RvD1 and RvE1 levels (Zhao et al, ) and by inhibiting phospholipase‐A2 (Mäkelä, Kuusi, & Schröder, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation